Paralytic ileus in a patient on clozapine therapy showing an inverted clozapine/norclozapine ratio after switching valproic acid to carbamazepine: a case report - Geke van Weringh; Leonieke van Koolwijk; Lieuwe de Haan; Daan J. Touw; Mariken B. de Koning (SAGE Publishing, 2024)
This case report examines the possible correlation between the clozapine/norclozapine ratio and the occurrence of constipation and paralytic ileus. We present the case of a 42-year-old patient diagnosed with schizoaffective disorder undergoing clozapine therapy. Despite intensive treatment with clozapine, haloperidol, valproic acid and biweekly electroconvulsive therapy sessions for over a year, florid psychotic symptoms and fluctuating mood swings persisted. Therefore, valproic acid was replaced by carbamazepine, a potent inducer of several CYP450-enzymes. To maintain clozapine plasma levels, fluvoxamine, a CYP1A2-inhibitor, was introduced at a dose of 25 mg before this switch. After addition of carbamazepine, there was a significant decline in clozapine levels, necessitating an increase in fluvoxamine dosage to 50 mg. Five weeks later the patient was admitted to a general hospital with a diagnosis of paralytic ileus. Treatment with enemas proved effective. Drug concentration analysis revealed a 2.5-fold increase in norclozapine levels in the weeks preceding hospital admission, resulting in an inverted clozapine/norclozapine ratio. Treatment with clozapine, carbamazepine and fluvoxamine was continued as the patient demonstrated clinical improvement on carbamazepine. Concurrently, an intensive laxative regimen was initiated. Two weeks later, the patient was readmitted to the general hospital due to suspected paralytic ileus and faecal vomiting, once again displaying an inverted clozapine/norclozapine ratio. We discuss potential mechanisms contributing to the occurrence of the paralytic ileus in this patient, including the antagonism of muscarinic M3 receptors by both clozapine and norclozapine, as well as the agonism of delta-opioid receptors by norclozapine. This case highlights the potential significance of both the clozapine/norclozapine ratio and absolute norclozapine levels as risk factors for constipation and paralytic ileus in patients on clozapine therapy.